An Asymptotic Theory of Growth Under Uncertainty - Merton, Robert C. (Review of Economic Studies, 1975)
Journal Article An Asymptotic Theory of Growth Under Uncertainty Get access Robert C. Merton Robert C. Merton Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 3, July 1975, Pages 375–393, https://doi.org/10.2307/2296851 Published: 01 July 1975